1993
DOI: 10.4315/0362-028x-56.9.788
|View full text |Cite
|
Sign up to set email alerts
|

Antibotulinal Properties of Selected Aromatic and Aliphatic Aldehydes

Abstract: Aromatic and aliphatic aldehydes were tested for their effectiveness against Clostridium botulinum spores and cells. Six-tenths millimolar benzaldehyde, piperonal, phenylacetaldehyde, α-amylcinnamaldehyde, vanillin, or phenylglyoxal delayed germination in botulinal assay medium (BAM) broth after 6 h exposure at 32°C. Sporicidal activity was observed with 1.25 mM vanillin, 39 mM isobutyraldehyde, 156 mM pyruvaldehyde or valeraldehyde, 625 mM benzaldehyde, and 2,500 mM α-amylcinnamaldehyde. Twenty-five millimola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…Nevertheless, it has been proposed that the chemical structure, such as the presence of the functional hydroxyl (-OH) group and the aromaticity are also responsible for the antibacterial activity [2,47,48].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Nevertheless, it has been proposed that the chemical structure, such as the presence of the functional hydroxyl (-OH) group and the aromaticity are also responsible for the antibacterial activity [2,47,48].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The report also indicated no genotoxic or mutagenic effects due to TC. The antibacterial activity of TC against Clostridium botulinum (Bowles and Miller, 1993), S. aureus (Bowles et al, 1995), E. coli O157:H7 and Salmonella Typhimurium (Helander et al, 1998) has been previously reported. Although, cinnamon or cinnamon oil has been used for ages in the treatment of UTIs, no scientific study was undertaken to investigate its antimicrobial efficacy against uropathogens.…”
Section: Trans-cinnamaldehydementioning
confidence: 85%
“…Carvacrol is bactericidal to Bacillus cereus at concentrations of 1.5 to 2 mM (9). Addition of 0.15 mM of carvacrol also disjoined membrane potential (10,11). When the effects of carvacrol on the growth of B. cereus were compared with the effects of the related molecule, it was found which concentration of the molecules possessing the hydroxyl group were needed to the growth suppression (12).…”
Section: Discussionmentioning
confidence: 96%